‘Pro-Life Feminism’? Contemporary Rhetoric of Organized Abortion Opposition in Germany - Juliette Brillet Reutter (Redescriptions)
Opposing abortion with arguments centered around the supposed best interest of women might seem counter-intuitive but has been identified as a common strategy of ‘pro-life’ movements around the globe. Drawing from interviews conducted with German ‘pro-life’ women, this article proposes to analyze a ‘pro-life feminist’ rhetoric, in which specific ideas of equality, structural discrimination, empowerment, and care-work serve to incriminate abortion in new ways. Adapting to current subjectivities while at the same time holding on to traditional views on gender, sexuality, and family allows for ‘pro-life’ activists to strive toward a future in which they wish abortion to no longer exist.